Do Bonuses Offset the Allocative Effects of Downward Rigid Base Wages? - Anne Kathrin Funk; Kaufmann, Daniel (My University, 2022)
We measure the labor market outcomes of employees with downward rigid base wages after an unexpected deflationary shock in Switzerland using a firm survey matched with Social Security register data. The employees that additionally receive downward flexible compensation, such as bonuses, are less likely to lose their job after a deflationary shock than those only receiving a base wage. Only a modest share of employees receives downward flexible compensation, however. Therefore, these compensation schemes do not offset the overall allocative effects of downward rigid base wages.